THE EFFECTS OF EMERGENCY SITUATIONS ON FRUIT PRODUCTION AND PURCHASE PRICES IN POLAND - Sylwia Kierczyńska (Annals of the Polish Association of Agricultural and Agribusiness Economists)
In recent years, in Poland there have been emergency situations causing difficulties and threats to fruit producers. In 2007 and 2017 there were severe frosts during the flowering period of fruit trees and shrubs. In 2014 the Russian Federation introduced an embargo on the import of agricultural products from the EU member-states. In 2020 there was the COVID-19 pandemic. In February 2022 Russia started war against Ukraine. The aim of this study was to assess changes in the level of fruit yields and purchase prices in the years when the aforementioned emergency situations occurred, to determine whether they led to fruit production crises in Poland, and to assess the ways the crises were overcome. In order to assess the strength of the crisis, deviations of the yield and purchase prices of selected fruits (apples, sour cherries, raspberries, and blackcurrants) from the average of the four years preceding the occurrence of the emergency situation were calculated. The study showed that the emergency situations caused by spring frosts were accompanied by fruit yield losses. However, this did not lead to a fruit production crisis, because lower yields were compensated by higher fruit purchase prices. In 2014 the Russian embargo on apples increased the supply of these fruits, which led to a decrease in their purchase prices. In order to counteract the crisis, fruits were withdrawn from the market. The COVID-19 pandemic drew consumers’ attention to healthy nutrition. Consumers became more interested in eating fruit and the prices of superfruits (raspberries, blackcurrants) increased. Military operations caused disruptions in international trade and changes in fruit purchase prices in Poland. The emergency situation caused by the war in Ukraine was accompanied by higher import of fruit products from that country and a decrease in the purchase prices of fruit (mainly raspberries) in Poland.